The Perpetuation of Muslim–Hindu Divide in British India Through the (Ab)Use of Historical Memory - Belmekki, Belkacem (Journal of Asian and African studies, 2025)
This article seeks to highlight the extent to which recounting historical narratives can determine the nature of relations between racial and ethnic groups, through examining the case of Muslims and Hindus in British India. Throughout the 19th century, the process of the religious communalization of the subcontinent was set in motion, which ultimately led to the bifurcation of the local society into two self-conscious, mutually antagonistic groups: a Hindu majority versus a Muslim minority. This study argues that such schism would not have taken place without the instrumentalization of a colonially ‘constructed’ past by Hindu communalists who, in the process of mobilizing their co-religionists through mythmaking and a hostile discourse fraught with subjectively interpreted historical facts, alienated the members of the other group. This article also underscores that besides imperial scholars, Hindutva activists should bear the historical responsibility for the divide.